Feasibility Study of Tobacco Farming in Patrang District, Jember Regency - Aulia Nadhirah; Tia Sofiani Napitupulu; Sumarlina Sumarlina; Dinu Saadilah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
Tobacco is one of the leading commodities in the agricultural sector. Tobacco is developed in several areas in Jember Regency, one of which is in Patrang District. This study aims to determine the use of production inputs in tobacco farming, production and productivity, income, and the feasibility of tobacco farming in Patrang District. Determination of the sample using a simple random method. The data were analyzed using descriptive analysis, farming income analysis, and farming feasibility analysis. The results of the analysis showed that (1) tobacco farmers in Patrang District use inputs of seeds, fertilizers, drugs, pesticides, tools and labor in carrying out tobacco farming; (2) the average production and productivity of tobacco per hectare is 4.42 ton and 0.96 ton/ha; (3) the average profit of tobacco farming is IDR 22.546.992,19; and (4) tobacco farming is feasible to develop that it can be seen from the R/C value is 2.4, the price BEP value is IDR 3,664 and the production BEP is 1,056 kilograms.